Case Report: Optimum excision with split skin graft closure in the management of penile sebaceous carcinoma - Fam, Xeng Inn; Liu, Chian Yong; Md Pauzi, Suria Hayati; Rizuana, Iqbal Hussain (Frontiers in Oncology, 2023)
Sebaceous carcinoma (SC) is a rare malignant skin neoplasms derived from the meibomian gland of adnexal epithelium, which is frequently confused with basal cell carcinoma (BCC) exhibiting sebaceous differentiation, and commonly found in the head and neck region. We report a case of penile sebaceous carcinoma, an extremely rare anatomical site for SC. A 68-years-old man presented with four-month history of painless, non-healing ulcerated nodule over the left side of the penile shaft. Wedged biopsy showed adenocarcinoma with signet ring differentiation. We proceeded with wide local excision (WLE) of the lesion with inclusion of the indurated skin and 5mm of normal margin, followed by primary closure of scrotal defect and split skin grafting of penile shaft using thigh skin donor. Final histopathological examination revealed sebaceous carcinoma with pagetoid spread. Patient achieved recurrent free survival without any form of adjuvant therapy after 4 years of follow-up.